Brain Source Localization in the Presence of Leadfield Perturbations - Momin, Rabiya Nakhat (2015)
A Master of Science thesis in Electrical Engineering by Rabiya Nakhat Momin entitled, "Brain Source Localization in the Presence of Leadfield Perturbations," submitted in May 2015. Thesis advisors are Dr. Hasan Mir and Dr. Hasan Al-Nashash. Soft and hard copy available.